Outcome of treatment of proximal tibial plateau fractures by minimally invasive percutaneous plating osteosynthesis technique - Kancherla, Nageswara Rao; Asif Hussain, Khazi Syed; Sreenath, Mukthapuram; Chilakamarri, Vijaya Krishna (International Journal of Research in Orthopaedics, 2016)
Background: Fractures of the proximal tibia are accompanied by a wide range of severity which may include stable undisplaced fractures with minimal soft tissue injury to highly comminuted unstable fractures, and severe soft tissue involvement. With the better understanding of fracture healing biology and biomechanics of fracture fixation and healing, the trend of treatment is towards biological fixation, which can be accomplished by Minimally Invasive Percutaneous Plating Osteosynthesis (MIPPO) technique. Methods: Demographic data of patients were recorded on admission and thorough history and clinical examination was done. The fractures were assessed for soft tissue injuries and followed by radiological assessment of fracture with schatzkers classification. The surgeries included anterolateral and anteromedial approaches for all patients with ‘inverted hockey stick incision’ and were treated with MIPPO. They were regularly followed up at 6-8 weeks interval till complete fracture union. A clinical and radiological evaluation was carried out using the modified Rasmussen clinical and radiological criteria. Results: Out of the 20 patients treated, most of them were males and belonged to the age group of 20-40 years (75%). Unilateral fractures were more common than bilateral fractures and were of the type 4 and type 5 of Schatzkers classification which was usually associated with high velocity RTA. One patient each had infection, varus deformity and knee joint stiffness. 10 fractures gave excellent result, 7 fractures healed with good results. Only 2 of the patients showed fair results and 1 had poor result. Conclusions: All the fractures treated with MIPPO technique was found to be rapidly healing by secondary fracture union and hence achieving strong bone union across the fracture site due to inherent benefits of less tissue damage and minimal disturbance of fracture site biology.